Full-automated Medical Imaging System for Segmentation and Detection of Carotid Plaque and Carotid Artery lumen From Ultrasound Images - Loizou, Christos P.; Spyrou, Christina; Pantziaris, Marios; Kasparis, Takis; Christodoulou, Lakis (My University, 2012)
The full segmentation and detection of the common carotid artery (CCA) in ultrasound images is important for the evaluation of the intima media thickness (IMT) and for the measurement of the artery stenosis. The IMT as well as the stenosis are considered to be the significant markers for the clinical evaluation of the risk of stroke. The current research proposes full-automated medical imaging system for the segmentation and detection of the CCA and the common artery lumen (CAL), which is based on an adaptive snake-contour segmentation algorithm. The CCA is segmented by the proposed algorithm into different distinct regions, namely the IMT, intima-media (IL), media-layer (ML), carotid plaque and lumen.
Keywords: Engineering; Computer and Information Sciences; Medical Informatics; Automated medical imaging system; Carotid plaque; Carotid artery; Ultrasound images